The Relative Merits of Cord Blood as a Cell Source for Autologous T Regulatory Cell Therapy in Type 1 Diabetes - Theil, A.; Wilhelm, C.; Guhr, E.; Reinhardt, J.; Bonifacio, E. (Hormone and Metabolic Research, 2015)
Cord blood has been used as a cell source for therapeutic purposes in children with type 1 diabetes and other disorders. Here, we explore the benefits of cord blood as an autologous source of T regulatory cells for immune cell therapy in patients. CD4+CD25+ T regulatory cells were isolated from cord blood and adult peripheral blood of healthy donors and compared during and after expansion in a 14-day protocol incorporating anti-CD3/anti-CD28 beads, and IL-2 with or without rapamycin. Cord blood T regulatory cells were largely naïve (89±7 vs. 31±10% in young adults, p<0.0001), and had higher expansion yields (median 5 968-fold) than adult T regulatory cells (median 516-fold, p=0.001) and adult naïve T regulatory cells (median 820-fold, p=0.003). Rapamycin reduced expansion yields, but was not necessary to obtain pure expanded cord blood T regulatory cells as judged by FOXP3 staining (94±3%), methylation status of FOXP3 (97%), and intracellular effector cytokine staining (< 6%). Expanded adult T regulatory cells were much less pure in the absence of rapamycin (72±19% FOXP3; 76% by methylation status, <13% INF-γ, <16% IL-4, <5% IL-17 positive), but purity was achieved by inclusion of rapamycin during expansion. Despite differences in purity, all preparations of expanded T regulatory from all sources were able to strongly suppress proliferation of T effector cells in vitro. Our findings suggest that cord blood is an excellent source of T regulatory cells for expansion and autologous cell therapy that may be considered as a strategy to prevent immune-mediated destruction of beta cells in type 1 diabetes.
Keywords: regulatory T cells; regulatory T cell therapy; diabetes mellitus type 1; autologous cord blood